Efficacy and tolerability of zinc acetate for treatment of chronic refractory cough: pilot randomised futility trial - Aparna Balasubramanian; Janet T. Holbrook; Brendan J. Canning; Loretta G. Que; Mario Castro; Barry J. Make; Linda Rogers; Michael F. Busk; Alexis Rea; Ashley A. McCook-Veal; Jiaxian He; Meredith C. McCormack; et al. (ERJ Open Research, 2023)
Background: Cough is the most reported symptom in the United States, with chronic refractory cough representing significant morbidity to patients. Zinc acetate may have beneficial effects in the cough reflex pathway. We sought to assess the safety and efficacy of zinc acetate in the management of chronic refractory cough. Study design and methods: This was a randomised, placebo-controlled, parallel-design pilot trial of individuals with chronic refractory cough. The effects of 6 weeks of zinc acetate versus placebo on quality of life and symptoms as measured by the Cough Quality-of-Life Questionnaire (CQLQ), Leicester Cough Questionnaire (LCQ), cough visual analogue score (C-VAS) and Global Assessment of Change in Cough (GACC) scores were evaluated. A futility analysis plan with a one-sided 80% confidence interval was used to compare treatment effect to published minimum clinically important differences (MCID) for each outcome. Results: 34 participants, 17 in each group, were enrolled and randomised. Participants were primarily white females with moderate–severe cough. Participants assigned to zinc acetate had a significant increase in serum zinc levels after 6 weeks, while those assigned to placebo did not. Both groups showed improvement in CQLQ, LCQ, C-VAS and GACC scores, but the treatment effects of zinc acetate versus placebo were small with confidence intervals that did not include the MCIDs. Interpretation: We observed no benefit of zinc therapy over placebo on cough symptoms or quality of life and conclude that larger trials of zinc for chronic cough are not warranted.